Approaches to systemic functional grammar : convergence and divergence - Tucker, Gordon H. (Gordon Howard), 1945-; Huang, Guowen, 1956-; Fontaine, Lise; McDonald, Edward, 1963- (Sheffield, South Yorkshire ; Bristol, CT : Equinox Publishing Ltd, 2020)
"This volume brings together contributions to a key area of interest within the framework of systemic functional linguistics: the role of meaning in the lexicogrammar. A key figure in the debate on this role is Robin Fawcett who has long argued for a fully semantic lexicogrammar where the relevant systems are seen as representing 'choices between meanings'. This volume, a festschrift in honour of Fawcett's long-standing contribution to the field, raises important questions related to lexicogrammatical meaning within systemic functional linguistics by examining the meaning-form interface, lexicogrammatical meaning in theme and transitivity, as well as lexis, intonation and its role in computational models. Importantly, discussions in the volume also explore the relationship between alternative approaches to systemic functional lexicogrammar, notably between the Hallidayan model and the Cardiff Grammar model developed primarily by Robin Fawcett"--
Includes bibliographical references and index.
Keywords: Functionalism (Linguistics); Semiotics